Strategi Kepala Sekolah dalam Mempertahankan Mutu Pendidikan pada Masa Pandemi Covid-19 di SMA Ar-Rahmah Malang - Burhana Rizky Pratama; Rodiyatin Puput T; Iffah Af'idah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2021)
Scholl is one of the aspects affected by the Covid-19 pandemic, therefore the importance of the strategy of educational institution leaders in maintaining the quality of their education so that they can always maintain their existance to the wider community, therefore this study has the aim to knowing the strategies applied by the head master of SMA Ar-Rahmah in maintaining the wuality of education during the Covid-19 pandemic. The methode used in this research is kualitative descriptive explanatory, information retrieval using structured interview with the principal as a resource. The information analysis that is tried in problem research is reduction, presentation, and the drawing of conclusions. The result found in this study are as follow: 1) the headmaster maintains the quality of this education by improving teacher professionalism by providing coaching and training such as saqofiyah coaching which aims to maintain the faith of teachers to carry out learning well, 2) during this pandemic the headmaster pas attention to the immunity of school residents by giving eclia test, using strict health protocols, both when the teacher enters the school environment and in the learning process, 3) the headmaster keeps the teaching and learning process going well by maintaining the health of students by providing additional foot to increase the immunity of participants students, besides providing additional activities to reduce the boredom of students in the teaching and learning process.